The Presentation Form of Mamözi Göndra Music In Accompanying Nias War Dance on Furai Studio of Medan - SIMAMORA, AGUSTYNUS SAPUTRA (Universitas Negeri Medan, 2017)
The result of this study indicates that the presence of music mamözi göndra which isinherited by their ancestors is still extant. A way of presenting music mamözi göndradivided into three sections: preparation before the music mamözi göndra performedbefore the word fahugo used , after fahugo used musical instruments mamözi göndraplayed together in the show, the process of closing music mamözi göndra done onlywith the code of the trainer music or göndra mamözi music artists . There are five musicfunctions mamözi göndra namely : The function of entertainment, self-expression,communication, a dance, economics. Göndra mamözi musical instruments used aregöndra as a carrier tempo and pulse, faritia as the carrier beats / pulse, aramba as aguide to determine the initial knock